Children living with their grandparents: resilience and wellbeing - Downie, Jill; Hay, David; Horner, Barbara; Wichmann, Helen; Hislop, Angela (Blackwell Publishing, 2009)
A non-comparative design and mixed-methods approach wasused to examine the resilience and wellbeing of 20 childrenin the full-time care of their grandparents. A self-reportmeasure of self-concept and emotional wellbeing, and asemi-structured interview were used to explore the personalexperiences and impact of children living with their grandparents.Scores derived from the self-report measure indicatedthat the children's self-worth and emotional health werewithin the range expected of children of comparative age andsex. Qualitative data, however, suggested a complex emotionalenvironment and a continuum of responses. Analysis revealedthree themes that captured broad issues around Emotionalhealth, Material factors, Current issues and Past experiencesand Coping strategies. The results of the study reveal the ongoingconcerns associated with the children's family circumstances,as well as the notable adaptation and resilience of the childrenin managing their life experiences.